2015
DOI: 10.1007/s00213-015-3880-7
|View full text |Cite
|
Sign up to set email alerts
|

Double dissociation of working memory and attentional processes in smokers and non-smokers with and without nicotine

Abstract: Nicotine has been shown to affect cortical excitability measured using transcranial magnetic stimulation in smoking and non-smoking subjects in different ways. In tobacco-deprived smokers, administration of nicotine restores compromised cortical facilitation while in non-smokers, it enhances cortical inhibition. As cortical excitability and activity are closely linked to cognitive processes, we aimed to explore whether nicotine-induced physiological alterations in non-smokers and smokers are associated with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
46
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 52 publications
6
46
0
1
Order By: Relevance
“…Rather than a blanket inability to engage cognitive and attentional resources, the deficit appears specific to conditions where only relatively minimal attention is required. The robust effects 14 on attention that we report are in line with literature on attention-enhancing effects of nicotine 14,41 and problems with sustained attention in smokers [42][43][44][45] .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Rather than a blanket inability to engage cognitive and attentional resources, the deficit appears specific to conditions where only relatively minimal attention is required. The robust effects 14 on attention that we report are in line with literature on attention-enhancing effects of nicotine 14,41 and problems with sustained attention in smokers [42][43][44][45] .…”
Section: Discussionsupporting
confidence: 89%
“…Some studies report worse cognitive control performance in smokers 30,31,47 , while others did not 33,48,49 . Studies manipulating satiety within-subject similarly reported mixed results for cognitive control tasks 42,44 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an enhancement of cortical-evoked potentials after prefrontal PAS25 was demonstrated via TMS-EEG 88 . Since cognitive functions that are affected by nicotine abstinence, such as working memory, episodic memory and attention 20 are related to the prefrontal cortex 8992 and can also be modulated by non-invasive brain stimulation protocols 93, 94 as well as nicotinic agents 13 , it would be relevant and feasible to focus the future exploration of nicotine withdrawal-related plasticity shifts directly on prefrontal cortex physiology.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from disturbed facilitatory plasticity, numerous studies in humans have reported that abstention from nicotine in smokers leads to deficits in working memory and attention 18, 19 , which are partially restituted by re-administration of nicotine or a α 4 β 2 nAChR agonists 2022 . However, in smoking humans the role of specific nAChRs in the re-establishment of impaired plasticity has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…; Grundey et al . ) in both animals and humans. Conversely, NIC withdrawal in tobacco smokers is often associated with the deterioration of working and verbal memory and neuroplasticity, whereas NIC re‐administration can restitute those withdrawal‐dependent deficits (Jacobsen et al .…”
Section: Introductionmentioning
confidence: 99%